Gender Recognition Of Transsexuals In Malaysia: Charting The Way Towards Social Inclusion - Siva Subramaniam, Mageswary; Ahmad, Asmida; Mohd Yusof, Yusnita; Ramzi Sulaiman, Nur Fazini Asro (2016)
Are you male or female? To most persons the answer to this question is given without any difficulty and with certainty. To transsexuals however the answer is unclear and the resulting uncertainties lead to social exclusion and marginalisation.Gender identity plays a pivotal role in a person’s daily life and affects a wide spectrum of sociolegal and conventional interactions ranging from the very mundane such as which public lavatory to use, to some of the most critical aspects of life such asemployment, education, marriage, healthcare and public persona.In Malaysia the absence of legalgender recognition for transsexuals post reassignment treatment has created a social environment which is unsustainable as it has resulted in social exclusion, inequality and prosecution. Objectives: To chart the way forward towards a more inclusive and socially just society there is a need to rethink thelegal framework pertaining to the gender recognition of transsexuals in Malaysia and deconstruct the perceived socioreligious and other limitations which are widely used to justify the present state of non - recognition. Methodology: Doctrinal legal research/qualitative. Analysis: Analysis of Article 3 & 8 of Federal Constitution of Malaysia, National Registration Act 1959,s. 66 of the Syariah Criminal (Negeri Sembilan) Enactment 1992, Gender Recognition Act 2004(UK) and relevant case laws. Conclusion: Proposals for comprehensive legislative reforms to set out guidelines for gender recognition of transsexuals in Malaysia.